2022
DOI: 10.1101/2022.05.04.490445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypereosinophilia causes progressive cardiac pathologies in mice

Abstract: Hypereosinophilic syndrome is a progressive disease with extensive eosinophilia that results in organ damage. Cardiac pathologies are the main reason for its high mortality rate. A better understanding of the mechanisms of eosinophil-mediated tissue damage would benefit therapeutic development. Here, we describe the cardiac pathologies that developed in a mouse model of hypereosinophilic syndrome. These IL-5 transgenic mice exhibited decreased left ventricular function at a young age which worsened with age. M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Previous studies have found that IL‐5 can regulate cardiac remodelling, such as improving cardiac remodelling after myocardial infarction and exacerbating cardiac remodelling induced by hypereosinophilia 33,34 . However, the regulatory role of IL‐5 in Ang II‐induced cardiac remodelling has not been reported.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have found that IL‐5 can regulate cardiac remodelling, such as improving cardiac remodelling after myocardial infarction and exacerbating cardiac remodelling induced by hypereosinophilia 33,34 . However, the regulatory role of IL‐5 in Ang II‐induced cardiac remodelling has not been reported.…”
Section: Discussionmentioning
confidence: 98%
“…15,[30][31][32] Considering that STATs are the most Previous studies have found that IL-5 can regulate cardiac remodelling, such as improving cardiac remodelling after myocardial infarction and exacerbating cardiac remodelling induced by hypereosinophilia. 33,34 However, the regulatory role of IL-5…”
Section: Discussionmentioning
confidence: 99%
“…The D2 model is limited in that it lacks the endocardial thrombosis, fibrosis, and systemic aspects typical of HES; furthermore, this model develops very early and resolves on its own by ~3 months of age 30 . Diny et al have shown that IL-5 transgenic mice develop worsening left ventricular function with age; however, no thrombosis or fibrosis was seen 28 . Studies in myosin-challenged IL-5 transgenic mice developed severe inflammation, followed by dilated cardiomyopathy and fibrosis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…As the NIH Taskforce on Research needs of Eosinophil-Associated Diseases (TREAD) and recent RE-TREAD reported, there is a paucity of preclinical models that adequately replicate cardiac disease in hypereosinophilia, and development of these models would enable mechanistic studies aiming to develop targeted therapies 8,9 . Attempts to model hypereosinophilia-associated heart disease in mice include spontaneous eosinophilic myocarditis in DBA/2 (D2) mice 27 , baseline heart disease in aging IL-5 transgenic mice 28 , and a model of antigen (cardiac myosin)-induced autoimmune EM elicited in IL-5 transgenic mice 12,29 . The D2 model is limited in that it lacks the endocardial thrombosis, fibrosis, and systemic aspects typical of HES; furthermore, this model develops very early and resolves on its own by ~3 months of age 30 .…”
Section: Discussionmentioning
confidence: 99%